(untitled) (European Bison Conservation Newsletter, 2012)
Editorial Office of the European Bison Pedigree Book (EBPB) is a keeper of pedigree database of European bison and the breeders/owners mainly from the years 1968–2012. The database includes information about the origin of animals, the state of world wisent population on 31st December of each year, together with changes which have occurred during last 12 months, and the current correspondence concerning the questions of pedigree. The digitized documents are available for interested breeders/owners with the consent of the Editorial Office of EBPB, in its office. The published annuals of European Bison Pedigree Book are available on website www.krz.bpn.com.pl The archive materials of the Internationale Gesellschaft zur Erhaltung des Wisents from the years 1924–1968 concerning the European bison breeding in Germany and in the world are also available with the consent of the Editorial Office of EBPB.